Catastrophic Head-Neck Dissociation of a Modular Cementless Femoral Component. Issue 3 (July 2015) - Swann, R. Presley; Webb, Jonathan E.; Cass, Joseph R.; Van Citters, Douglas W.; Lewallen, David G.
Abstract : Case: We report two cases of modular head-neck junction failure involving the Stryker Accolade TMZF stem leading to sudden dissociation of the femoral head from the stem. Both patients presented with mechanical symptoms in the hip followed by pain and hip dysfunction. Disassembly of the head and deformation of the male taper were seen on preoperative radiographs. Intraoperatively, both patients had substantial metallosis with a markedly damaged taper requiring stem revision. Conclusion: We recommend regular clinical and radiographic surveillance of patients with the Stryker Accolade TMZF stem, especially those patients with pain and/or mechanical symptoms.